Rendition - Golin, Steve; Viscidi, Marcus; Sane, Kelley; Hood, Gavin; Gyllenhaal, Jake, 1980-; Witherspoon, Reese, 1976-; Sarsgaard, Peter; Metwally, Omar.; Naor, Yigal; Khouas, Moa.; Oukach, Zineb; Arkin, Alan.; et al. (Burbank, CA : New Line Home Entertainment : Warner Home Video, 2008)
The policy of "extraordinary rendition" began under the Clinton administration and accelerated after September 11, 2001. The policy allows for the handing over of suspected terrorists to countries that use torture as an interrogation tool. Anwar El-Ibrahimi is an Egyptian-born man who disappears on a flight from Africa to Washington, DC. He is sent to a North African country where torture is practiced and the CIA gives approval. Anwar's pregnant American-born wife wants to know what happened to her husband. A reluctant CIA agent begins to question his assignment after witnessing an unorthodox interrogation. A severe interrogator plys his trade on Anwar while a U.S. terrorism honcho is willing to turn a blind eye to the unpleasantness, especially if it stops a terrorist attack.
DVD ; region 1 ; widescreen (2.35:1) presentation ; Dolby Digital 5.1 surround sound, stereo surround sound ; DVD-9.
In English with optional English or Spanish subtitles.
Closed-captioned.
Jake Gyllenhaal, Omar Metwally, Reese Witherspoon, Peter Sarsgaard, Yigal Naor, Moa Khouas, Zineb Oukach, Alan Arkin, Meryl Streep.
Director of photography, Dion Beebe ; editor, Megan Gill ; music, Paul Hepker, Mark Kilian ; costume designer, Michael Wilkinson ; production designer, Barry Robison.
DVD release of the 2007 motion picture.
Keywords: Political prisoners -- Abuse of -- Africa, North -- Drama; United States. -- Central Intelligence Agency -- Drama; Questioning -- Africa, North -- Drama; Terrorism -- Drama; Africa, North -- Drama; Delitos políticos -- Teatro; Preguntas y respuestas -- Teatro; Political prisoners -- Abuse of -- Africa, North -- Drama; United States. -- Central Intelligence Agency -- Drama; Question and answers -- Africa, North -- Drama; Terrorism -- Drama; Africa, North -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Films for the hearing impaired; Thriller -- Feature; Political -- Feature; Feature films; Suspense films